KELVIN PROBE’S STRAY CAPACITANCE AND NOISE SIMULATION - S. Danyluk; A. V. Dubanevich; O. K. Gusev; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky; R. I. Vorobey; A. L. Zharin (Приборы и методы измерений)
Stray capacitance effects and their influence on Kelvin probe’s performance are studied using mathematical and computer simulation. Presence of metal surface, even grounded, in vicinity of vibrating Kelvin probe produces the additional stray signal of complex harmonic character. Mean value and amplitude of this stray signal depends mostly on the ratio of stray and measurement vibrating capacitors gaps d1/d0. The developed model can be used for theoretical analysis of Kelvin probe configuration and probe electrometer’s input circuit.